2023
DOI: 10.1177/08968608231193240
|View full text |Cite|
|
Sign up to set email alerts
|

A multi-institutional, observational study of outcomes after catheter placement for peritoneal dialysis in Japan

Tsutomu Sakurada,
Shigeki Kojima,
Shohei Yamada
et al.

Abstract: Background: This multi-institutional, observational study examined whether the outcomes after peritoneal dialysis (PD) catheter placement in Japan meet the audit criteria of the International Society for Peritoneal Dialysis (ISPD) guideline and identified factors affecting technique survival and perioperative complications. Methods: Adult patients who underwent first PD catheter placement for end-stage kidney disease between April 2019 and March 2021 were followed until PD withdrawal, kidney transplantation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The prevalence of prior abdominal surgery in patients undergoing PD catheter insertion ranges from 22% to 59% in previous studies compared with 30% in this study. [13][14][15][16][19][20][21] Most of these studies do not report the prevalence of adhesions but rather the use of adhesiolysis, which ranges from 1% to 31% (mean 19%) compared with 11% in this study. Crabtree found that the number of prior surgeries and women were at higher risk for adhesiolysis.…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of prior abdominal surgery in patients undergoing PD catheter insertion ranges from 22% to 59% in previous studies compared with 30% in this study. [13][14][15][16][19][20][21] Most of these studies do not report the prevalence of adhesions but rather the use of adhesiolysis, which ranges from 1% to 31% (mean 19%) compared with 11% in this study. Crabtree found that the number of prior surgeries and women were at higher risk for adhesiolysis.…”
Section: Discussionmentioning
confidence: 91%
“…2,3 Published in this issue of Peritoneal Dialysis International is the first multi-centre study of outcomes after PD catheter placement in Japan, contrasting their results to the audit criteria suggested in the guidelines for PD access by the International Society for Peritoneal Dialysis (ISPD). 4,5 The study was comprised of 49 collaborating institutions performing 409 catheter placements by nephrologists (69.2%) and surgeons (30.8%) using laparotomy (87.8%) and laparoscopy (12.2%). Although the authors used the term catheter patency failure, the outcome was based upon the ISPD definition of probability of catheter survival at 12 months following placement where the catheter has not been removed, replaced or required some type of intervention (surgical or radiological) because of flow restriction or irremediable drain pain.…”
mentioning
confidence: 99%